ANALISIS TIME STUDY PADA RANCANG BANGUN ALAT APLIKATOR BITUMEN - Lokaputra, Riduwan; Faturrahman, Anugrah Krishna; irwan, Chasun (Jurnal Sains Ilmu Teknologi Industri, 2024)
ANR is one of the largest cable companies in Indonesia. The company produces many types of cables from low voltage, medium voltage, and high voltage which have a lot of interest from home scale to mass projects. In the process of making high voltage cables, especially in the IS-23 machine process, there are stages of bituminous coating which functions to prevent or inhibit the spread of corrosion on the armor layer so that the cables are more durable and protected. However, in the process of coating bitumen, there are obstacles in applying bitumen still using human power and with special tools. This study discusses changes to the standard output on the IS-23 machine both before and after the tool design is used in the production. This study uses the time study method to make an analysis about IS-23 both before and after the design of the tool is used in the production. the results of this study resulted in the standard output of the is-23 engine which was originally 610,27 m/shift to 1417,63 m/shift